Pulsed Radiofrequency Dorsal Root Ganglion-Fluoroscopy Guide for Lumbar Radicular Pain - Nugroho Wicaksono (Faculty of Medicine, Brawijaya University, 2021)
Background: Lumbosacral radicular pain is the most common neuropathic pain. Pulsed Radio Frequency (PRF) is a method that believes to be safe and effective for reducing pain.Case: A 43-year-old woman experiences chronic right lumbar radiculopathy due to Herniated nucleus pulposus (HNP) L4-5. Anamnesis and physical examination show a sign of neuropathic pain. The MRI examination shows a paracentral disc protrusion L4-5 that compresses the transversing nerve L5. The conservative management did not produce a satisfying result indicated by the patient still experience pain with the Numeric Rating Scale (NRS) 4-5. Patient unable to do activity properly. We perform pain management using the dorsal root ganglion L5 pulsed radiofrequency-fluoroscopy (PRF) and producing a positive outcome. Patients experience a decrease in pain intensity with NRS 1. The examination on one and two months post-intervention show an improvement. Patient able to do the daily activity with NRS 1-2.Conclusion: Pulsed radiofrequency dorsal root ganglion-fluoroscopy guide that relatively safe, minimum complications, and minimal side effects, making it the preferred treatment for chronic lumbar radicular pain.